Reintroduction of elective cardiac interventions in the era of COVID-19: the Barts experience - Anthony Mathur; Andreas Baumbach; Andrew Wragg; Oliver Guttmann; Dan Jones; Katrina Comer; Jonathan Lambourne; Michael Mullen; Stephen Hamshere; Fizzah Choudhry; Krishna Rathod; Gordon Mills; et al. (Open Heart)
Background The response to COVID-19 has required cancellation of all but the most urgent procedures; there is therefore a need for the reintroduction of a safe elective pathway.Methods This was a study of a pilot pathway performed at Barts Heart Centre for the admission of patients requiring elective coronary and structural procedures during the COVID-19 pandemic (April–June 2020). All patients on coronary and structural waiting lists were screened for procedural indications, urgency and adverse features for COVID-19 prognosis and discussed at dedicated multidisciplinary teams. Dedicated admission pathways involving preadmission isolation, additional consent, COVID-19 PCR testing and dedicated clean areas were used.Results 143 patients (101 coronary and 42 structural) underwent procedures (coronary angiography, percutaneous coronary intervention, transcatheter aortic valve intervention and MitralClip) during the study period. The average age was 68.2; 74% were male; and over 93% had one or more moderate COVID-19 risk factors. All patients were COVID-19 PCR negative on admission with (8.1%) COVID-19 antibody positive (swab negative). All procedures were performed successfully with low rates of procedural complications (9.8%). At 2-week follow-up, no patients had symptoms or confirmed COVID-19 infection with significant improvements in quality if life and symptoms.Conclusion We demonstrated that patients undergoing coronary and structural procedures can be safely admitted during the COVID-19 pandemic, with no patients contracting COVID-19 during their admission. Reassuringly, patients reflective of typical practice, that is, those at moderate or higher risk, were treated successfully. This pilot provides important information applicable to other settings, specialties and areas to reintroduce services safely.